2016
DOI: 10.1038/srep38199
|View full text |Cite
|
Sign up to set email alerts
|

Ascl3 transcription factor marks a distinct progenitor lineage for non-neuronal support cells in the olfactory epithelium

Abstract: The olfactory epithelium (OE) is composed of olfactory sensory neurons (OSNs), sustentacular supporting cells, and several types of non-neuronal cells. Stem and progenitor cells are located basally, and are the source of all cell types needed to maintain OE homeostasis. Here, we report that Ascl3, a basic helix-loop-helix transcription factor, is expressed in the developing OE. Lineage tracing experiments demonstrate that the non-neuronal microvillar cells and Bowman’s glands are exclusively derived from Ascl3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 37 publications
2
15
0
Order By: Relevance
“…Intermediate filaments: 14,15,and 19 Basal epithelial cells marked by the acidic cytokeratins KRT5 and 14 have been shown to mark progenitor cells of numerous epithelial tissues including skin, cornea, developing trachea, lung airway epithelia, bladder, and salivary glands (Colopy, Bjorling, Mulligan, & Bushman, Olfactory epithelium-gives rise to microvillar cells and Bowman's gland (Yoshida et al, 2001;Weng et al 2016) Olfactory epithelium-Ascl3-deficient mouse lacks the non-neuronal microvillar and Bowman's gland support cells (Weng et al 2016) KIT SG-duct cells (adult reported; Emmerson et al, 2018). SG-Kit-deficient E14 SG (Kit w/w ) has reduced epithelial branching ) Olfactory epithelium (Goss et al 2015) Lymphatics (Stanczuk et al 2015) Kidney-reductions in ureteric bud branching and nephrons (Kit w/w and via inhibition of c-kit tyrosine phosphorylation; (Ito et al 2005;Wang et al, 2011;Morris et al 2004) No Krt15-deficient studies reported KRT19 SG-not reported SG-No Krt19-deficient SG studies reported Exocrine pancreas, liver-duct cells (Means et al, 2008) Stomach, intestine (Means et al, 2008) No Krt19-deficient studies reported…”
Section: Progenitor Markers In Developing Sgmentioning
confidence: 99%
See 1 more Smart Citation
“…Intermediate filaments: 14,15,and 19 Basal epithelial cells marked by the acidic cytokeratins KRT5 and 14 have been shown to mark progenitor cells of numerous epithelial tissues including skin, cornea, developing trachea, lung airway epithelia, bladder, and salivary glands (Colopy, Bjorling, Mulligan, & Bushman, Olfactory epithelium-gives rise to microvillar cells and Bowman's gland (Yoshida et al, 2001;Weng et al 2016) Olfactory epithelium-Ascl3-deficient mouse lacks the non-neuronal microvillar and Bowman's gland support cells (Weng et al 2016) KIT SG-duct cells (adult reported; Emmerson et al, 2018). SG-Kit-deficient E14 SG (Kit w/w ) has reduced epithelial branching ) Olfactory epithelium (Goss et al 2015) Lymphatics (Stanczuk et al 2015) Kidney-reductions in ureteric bud branching and nephrons (Kit w/w and via inhibition of c-kit tyrosine phosphorylation; (Ito et al 2005;Wang et al, 2011;Morris et al 2004) No Krt15-deficient studies reported KRT19 SG-not reported SG-No Krt19-deficient SG studies reported Exocrine pancreas, liver-duct cells (Means et al, 2008) Stomach, intestine (Means et al, 2008) No Krt19-deficient studies reported…”
Section: Progenitor Markers In Developing Sgmentioning
confidence: 99%
“…However, whether KRT5 and KRT14 cells contribute to the synthesis of ASCL31 cells or if this is a population of cells that arises from another progenitor cell type remains to be investigated. Furthermore, ASCL31 cells exclusively give rise to microvillar cells and Bowman's glands of the olfactory epithelium (Weng, Vinjamuri, & Ovitt, 2016).…”
Section: Growth Factor Receptors: Kit and Lgr4/5/6mentioning
confidence: 99%
“…The mature mouse OE is a pseudostratified epithelium consisting of three main cell types, the nuclei of which are located in different layers: sustentacular cell (Sus, a supporting cell population) nuclei in the apical layer, ORN nuclei in the middle layers, and basal cell (BC, progenitors that give rise to Sus cells and ORNs) nuclei in the basal layer (Murdoch and Roskams, 2007;Schwob et al, 2017). Other OE cell types include Bowman's duct cells and microvillar cells (Weng et al, 2016). OE development and neurogenesis occur in two main phases: embryonic day 10 (E10) to E13 and E13 to adult (Beites et al, 2005;Ikeda et al, 2007;Smart, 1971).…”
Section: Introductionmentioning
confidence: 99%
“…One possible explanation is that p75NTR might be involved in the development and maintenance of cholinergic TRPM5-MCs since cholinergic neurons in the brain require NTs for proliferation, differentiation and maturation [ 47 , 48 ]. TRPM5-MCs differentiate from a distinct progenitor lineage expressing the transcription factor ASCL3 [ 15 ]. The lack of TRPM5-MCs in Skn-1a −/− mice may diminish such a need for such NT-mediated regulation.…”
Section: Discussionmentioning
confidence: 99%
“…One such mechanism is adult neurogenesis, which involves globose and horizontal basal cells residing in the basal compartment of the olfactory epithelium [ 13 ]. These progenitor cells give rise to immature and mature OSNs as well as non-neuronal SCs and MCs, including TRPC6-MCs and TRPM5-MCs [ 14 , 15 , 16 ]. Thus, the basal cells play an important role in injury-triggered MOE repair and also adult regeneration for homeostatic maintenance.…”
Section: Introductionmentioning
confidence: 99%